The epic fail of Arturo Zamora - Cartaya, Pablo (Viking, 2017)
When his family's restaurant and Cuban American neighborhood in Miami are threatened by a greedy land developer, thirteen-year-old Arturo, joined by Carmen, a cute poetry enthusiast, fight back, discovering the power of poetry and protest through untold family stories and the work of José Martí.